Marital status and risk of type 2 diabetes among middle-aged and elderly population: a systematic review and meta-analysis - Mohammad Amin Karimi; Sara Binaei; Seyed Hadi Hashemi; Pegah Refahi; Ensiyeh Olama; Elnaz Olama; Aydin Mohammadpour; Reza Mostafaei Yonjali; Mohadeseh Poudineh; Niloofar Deravi (Frontiers in Medicine)
BackgroundMarital status is among the factors influencing type 2 diabetes mellitus (T2DM). However, the precise relationship remains incompletely understood. This meta-analysis aims to evaluate the association between marital status and the incidence of T2DM.MethodsA review and meta-analysis of observational studies were conducted to investigate the relationship between marital status and diabetes incidence. We searched three databases, including PubMed, Google Scholar, and Scopus, for relevant studies published up to August 16th, 2023. In our initial search, we identified a total of 358 articles. After a demanding screening process involving evaluating titles, abstracts, and full-text content, we ultimately included six studies for our meta-analysis.ResultComprising a total of 1,440,904 participants, our study found that in comparison to married individuals, unmarried participants exhibited a higher likelihood of developing diabetes [odds ratio (OR): 1.47, 95% confidence interval (CI): 0.88–2.45, I2: 91%, p-value = 0.14]. Divorced participants had a reduced likelihood of developing diabetes compared to married participants (OR: 0.84, 95% CI: 0.77–0.91, I2: 17%, p < 0.001). Similarly, widowed participants showed a lower risk of developing diabetes compared to divorced participants (OR: 0.35, 95% CI: 0.26–0.46, I2: 83%, p < 0.00001).ConclusionThis study provides strong evidence of links between marital status and type 2 diabetes risk. Unmarried individuals are more susceptible to T2DM, divorced individuals have a lower risk, and widowed individuals exhibit reduced T2DM risk. Further research should investigate underlying mechanisms and confounding factors.